POLA PENYEBARAN KEPITING BIOLA (Uca sp.) DI KAWASAN MANGROVE CURAHSAWO PROBOLINGGO, JAWA TIMUR - Agung Riswandi; Uun Febriyani (Universitas Sumatera Selatan, 2022)
One type of crab that has habitat in intertidal areas is the Violin Crab (Uca sp.)l, especially around the mangrove forest area. This research was conducted in the mangrove area of Curahsawo, East Java in April 2020. The purpose of this study was to determine the structure of the Violin Crab community in the mangrove area of Curahsawo Probolinggo. Parameters measured were soil pH, soil organic matter and soil texture. There are 3 sampling points, namely station 1 in the mangrove area, station 2 in the pond area, and station 3 in the estuary area. The results of environmental quality measurements at the research location were that the highest soil pH was around 8.03, while the highest soil organic matter was 3.106%, and the soil types were dusty clay and sandy loam. Uca rosea, Uca lactea, Uca vocans, Uca perplexa, Uca dussumieri, Uca demani are 6 types of violin crabs found in the Curahsawo mangrove ecosystem. , Uca demani and grouped for Uca rosea and Uca perplexa. The results of the distribution of violin crabs on the type of soil texture were very visible in the scattered Uca perplexa crabs because at all soil sampling points the highest number was 16 ind/m2 in both types of soil textures.